Economic tradeoff analysis of a product line architecture approach through model-based systems engineering: a case study of future mine countermeasures unmanned underwater vehicles - Alves, João Franklin Silva Brasilino Pacheco (2022)
The defense sector often develops systems to operate for at least 15 years, which can reach 40 or even 50 years. Those systems tend to be cheaper, more rapidly developed, and reliable when developed on product lines (PL). Product line architecture surges with potential to improve the acquisition process, resulting in a more rapid insertion of cost-effective warfighting capabilities. This thesis investigates the impact of the PL approach by analyzing the future generation of mine countermeasure (MCM) unmanned underwater vehicle (UUV) architecture alternatives, employing a detailed reuse model based on the COPLIMO framework. The research integrates parametric cost modeling with model-based systems engineering (MBSE), feeding the existing baseline knowledge regarding PL architecture. Furthermore, this can improve systems acquisition processes, deliver more agile capability, and reduce total life cycle costs (LCC). The integration of models highlights significant differences among the architectural variations considered early in the acquisition process before substantial financial commitments. Early decisions determine most of the total LCC and establish a baseline for long-term system performance. Hence, the choice of favorable design alternatives is crucial to program success. The results demonstrate that up-front investments in product lines generate a significant return on investment (ROI).